Isopropoxy Benzene Guanidine Kills Staphylococcus aureus Without Detectable Resistance - Zhang, Xiufeng; Xiong, Wenguang; Peng, Xianfeng; Lu, Yixing; Hao, Jie; Qin, Zonghua; Zeng, Zhenling (Frontiers in Microbiology, 2021)
Serious infections caused by multidrug-resistant Staphylococcus aureus clearly urge the development of new antimicrobial agents. Drug repositioning has emerged as an alternative approach that enables us to rapidly identify effective drugs. We first reported a guanidine compound, isopropoxy benzene guanidine, had potent antibacterial activity against S. aureus. Unlike conventional antibiotics, repeated use of isopropoxy benzene guanidine had a lower probability of resistance section. We found that isopropoxy benzene guanidine triggered membrane damage by disrupting the cell membrane potential and cytoplasmic membrane integrity. Furthermore, we demonstrated that isopropoxy benzene guanidine is capable of treating invasive MRSA infections in vivo studies. These findings provided strong evidence that isopropoxy benzene guanidine represents a new chemical lead for novel antibacterial agent against multidrug-resistant S. aureus infections.